Effect of repeating hydrothermal growth processes and rapid thermal annealing on CuO thin film properties - Ozga, Monika; Zielony, Eunika; Wierzbicka, Aleksandra; Wolska, Anna; Klepka, Marcin; Godlewski, Marek; Kowalski, Bogdan J.; Witkowski, Bartłomiej S. (Beilstein Journal of Nanotechnology, 2024)
This paper presents an investigation into the influence of repeating cycles of hydrothermal growth processes and rapid thermal annealing (HT+RTA) on the properties of CuO thin films. An innovative hydrothermal method ensures homogeneous single-phase films initially. However, their electrical instability and susceptibility to cracking under the influence of temperature have posed a challenge to their utilization in electronic devices. To address this limitation, the HT+RTA procedure has been developed, which effectively eliminated the issue. Comprehensive surface analysis confirmed the procedure’s ability to yield continuous films in which the content of organic compounds responsible for the formation of cracks significantly decreases. Structural analysis underscored the achieved improvements in the crystalline quality of the films. The implementation of the HT+RTA procedure significantly enhances the potential of CuO films for electronic applications. Key findings from Kelvin probe force microscopy analysis demonstrate the possibility of modulating the work function of the material. In addition, scanning capacitance microscopy measurements provided information on the changes in the local carrier concentration with each repetition. These studies indicate the increased usefulness of CuO thin films obtained from the HT+RTA procedure, which expands the possibilities of their applications in electronic devices.
Keywords: CuO; hydrothermal method; rapid thermal annealing; thin films